The Use of Think-Pair-Share With Inspiring Videos On Students’ Language Acquisition: A Preliminary Research - Muhammad Guruh Nuary (Prosiding University Research Colloquium, 2018)
One of the problem of students that learning language especially forEnglish subject is the less of vocabulary which they have. In thispaper, researcher will conducted a research that use think-pair-sharein the class, which is may help students to get more English words.Researcher also use inspiring videos to increase their motivation tolearn English more. This research, use qualitative approach withpreliminary research method to gathered the data from previousstudy, field observation and also from interview students and teacherin the end of the class activity. This preliminary research wasconducted at SMAN 1 Pabedilan, Cirebon. In this research,researcher take two classes in tenth grade, MIA 1 and MIA 3.Researcher took 10 students of each class of MIA 1 and MIA 3. Theresult are students feel bored during the class, students feel they cannot mastery the English well, etc. For the teacher, using anothermodel, method or strategy is not really important to do. In thisresearch, researcher will conduct the use of Think-Pair-Share in theclassroom, perhaps with inspiring videos can make languageacquisition of students increase and for students motivation to learnEnglish either.